Seasonality in the vertical flux and species composition of Radiolaria Polycystina (Protista): Patterns and drivers - Boltovskoy, Demetrio (2017)
Radiolarian flux rates, their intermittency, and changes in their species compositions are assessed using data from 73 time-series sediment trap deployments (1357 samples) covering 7-12 calendar months. Results are analyzed as a function of trap depth, latitude, and seasonal and geographic variations in sea surface temperature and primary production. Radiolarian flux rates are highest in the tropics and subtropics, decreasing towards the high latitudes. Low and highly intermittent primary production (PP) regimes are reflected in more pulsating radiolarian flux rates, but in moderate to high PP areas, radiolarian fluxes are not associated with phytoplanktonic growth cycles. At sites where simultaneous trap deployments at different depths were performed, shallower traps yield lower and more pulsating radiolarian flux values than deeper ones. Enhanced dissolution of biogenic silica in the shallower traps is probably responsible for these differences. Intermittency in radiolarian flux is highest in the seasonally ice-covered Southern Ocean waters, but much lower in the also seasonally ice-covered northern hemisphere sites investigated, suggesting differences in the mechanisms that govern the production and recycling of organic matter in the upper ocean and at mid depths. Radiolarian flux rates and their species richness do not seem to be coupled, neither temporally nor geographically. Temporal stability in the composition of the radiolarian taxocoenoses is generally high, and positively associated with absolute flux values and trap depth. The bulk of the assemblages are little affected by environmental seasonality, and only a few species, albeit often numerically dominant, seem to reflect these changes.